2019
DOI: 10.1101/745885
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An impressive capacity for cold tolerance plasticity protects against ionoregulatory collapse in the disease vector,Aedes aegypti

Abstract: 141. The mosquito Aedes aegypti is largely confined to tropical and subtropical regions but its 15 range has recently been spreading to colder climates. As insect biogeography is closely 16 tied to environmental temperature, understanding the limits of Ae. aegypti thermal 17 tolerance and their capacity for phenotypic plasticity is important in predicting the spread 18 of this species. 19 2. In this study we report on the chill coma onset and recovery, as well as low temperature 20 survival phenotypes of la… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
(90 reference statements)
0
4
0
1
Order By: Relevance
“…Mosquitoes have evolved various strategies to cope with different thermal conditions such as acclimation, adjusting behavioural activity and synthesis of heat shock proteins [54][55][56]. The downregulation at 32°C and 7 dpi of two sensory genes, namely odorant binding protein and long wavelength opsin, suggest a possible effect on mediators of behavioural activity.…”
Section: Discussionmentioning
confidence: 99%
“…Mosquitoes have evolved various strategies to cope with different thermal conditions such as acclimation, adjusting behavioural activity and synthesis of heat shock proteins [54][55][56]. The downregulation at 32°C and 7 dpi of two sensory genes, namely odorant binding protein and long wavelength opsin, suggest a possible effect on mediators of behavioural activity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that Ae. aegypti larvae from a colony maintained at 22 ± 1°C continued to move in response to probing as the temperature was gradually lowered; the larvae did not stop responding with movement until the temperature reached 6°C, 16°C lower than the temperature at which their colony was maintained (Jass et al, 2019). From a public health perspective, the absence of significantly lower predation efficiency at lower temperatures is useful because Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is evident that the life cycle of the mosquitoes in Londrina is also affected only in extreme temperatures, in view of the greater number of emergencies of adults of A. aegypti observed at 5°C (44.80%), as well as a relatively low mortality rate on this temperature (6.6%). The ability of A. aegypti larvae and adult to tolerate low temperatures also was demonstrated in the study by Jass et al [41].…”
Section: Discussionmentioning
confidence: 68%